Microstructure analysis of aluminium metal matrix alloy with silicon carbide and hexogonal boron nitride - Talib, Norfazillah; Nagarajan, Sugan; Lee, Woon Kiow; Saleh, Aslinda; Abdullah, Haslina (Penerbit UTHM, 2020)
Aluminum metal matrix composite (AMMCs) are considered a group of new advance material for its light, weight, high strength, modulus, low co-efficient of thermal expansion and good wear properties. In recent years, Metal Matrix Composite (MMCs) have attracted much attention due to excellent mechanical properties such as high specific strength and wear resistance (Poletti et al., 2008). AMMCs are widely used in aircraft, aerospace, automobile and various others field. The MMCs encompasses a wide range scale and microstructure. MMCs could be a material with a least two constituent elements. One necessary to be metal whereas another could also be special metal or alternative material like reinforcement ceramic. Metal matrix composite attract great deal of attentions nowadays due to their great mechanical properties and also their application in advance industry. The network is bulk and nonstop material though support is short and end material improved into matrix. The reinforcement should be stable in given working temperature and non-reactive too. The most commonly used reinforcement are silicon carbide (SiC) and aluminum oxide (Al2O3). The primary function of the reinforcement in MMCs is to carry most of the applied load, where the matrix binds the reinforcement together, and transmit and distributes the external load to the individual reinforcement. Good wetting is an essential condition for the generation for satisfactory bond between particles between particles reinforcement. The composite microstructure may be subdivided, as depicted in, according to whether the reinforcement is in the form of continuous fibers, short fibers or particles.